Utilization of Cow Dung and Coconut Shell in Making Briquettes With Tapioca Strach Adhesive as Alternative Energy - Irawan, Nisya Indriyanti; Meiliyadi, Lalu Ahmad Didik (Jurnal Sains Dasar, 2024)
This research was conducted with the aim of producing briquettes that have quality in accordance with SNI, with the composition of cow dung and coconut shell materials so that they can be utilized as alternative energy. The core scheme of this research is to test the quality of charcoal, especially its calorific value. By using variables in the form of a mixture of cow dung and coconut shell used, for samples A: 30%, 70%, B: 40%, 60%, C: 50%, 50%, D: 30%, 70. Based on the data obtained, it can be concluded that the mixture that has the optimal value to get the best quality of briquettes is sample D, which is 30% cow dung and 70% coconut shell where the calorific value obtained is 4706 cal/g. Cow dung is very efficient to be used as biobriquettes